The Effect of Perceived Enjoyment on the Decision of Digital Payment Utilization in Millennial Generation - Karta Negara Salam; Muhammad Imam Taufik (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2020)
Digital payment is a payment method using electronic media. Someone can make payment transactions with a short message service (SMS), internet banking, mobile banking, or electronic wallet. This study aimed to analyze the effect of perceived enjoyment on the decision to use digital payments on the millennial generation in Makassar city. Respondents in this study were citizens of Makassar who use digital payment. The analysis technique used was descriptive analysis and simple linear regression. The results showed that perceived enjoyment had a positive and significant effect on the Millennials’ decision to use digital payment. It implies that the higher perceived enjoyment felt by Millennials in Makassar City, the higher the chance of their decision to utilize digital payment in transactions.